Efficacy and Safety of Botulinum Toxin Type A for Limb Spasticity after Stroke: A Meta-Analysis of Randomized Controlled Trials. (7th April 2019) - Sun, Li-Chun; Chen, Rong; Fu, Chuan; Chen, Ying; Wu, Qianli; Chen, RuiPeng; Lin, XueJuan; Luo, Sha
Abstract : Background . Inconsistent data have been reported for the effectiveness of intramuscular botulinum toxin type A (BTXA) in patients with limb spasticity after stroke. This meta-analysis of available randomized controlled trials (RCTs) aimed to determine the efficacy and safety of BTXA in adult patients with upper and lower limb spasticity after stroke. Methods . An electronic search was performed to select eligible RCTs in PubMed, Embase, and the Cochrane library through December 2018. Summary standard mean differences (SMDs) and relative risk (RR) values with corresponding 95% confidence intervals (CIs) were employed to assess effectiveness and safety outcomes, respectively. Results . Twenty-seven RCTs involving a total of 2, 793 patients met the inclusion criteria, including 16 and 9 trials assessing upper and lower limb spasticity cases, respectively. For upper limb spasticity, BTXA therapy significantly improved the levels of muscle tone (SMD=-0.76; 95% CI -0.97 to -0.55; P<0.001), physician global assessment (SMD=0.51; 95% CI 0.35-0.67; P<0.001), and disability assessment scale (SMD=-0.30; 95% CI -0.40 to -0.20; P<0.001), with no significant effects on active upper limb function (SMD=0.49; 95% CI -0.08 to 1.07; P=0.093) and adverse events (RR=1.18; 95% CI 0.72-1.93; P=0.509). For lower limb spasticity, BTXA therapy was associated with higher Fugl-Meyer score (SMD=5.09; 95%CI 2.16-8.01; P=0.001), but had no significant effects on muscle tone (SMD=-0.12; 95% CI -0.83 to 0.59; P=0.736), gait speed (SMD=0.06; 95% CI -0.02 to 0.15; P=0.116), and adverse events (RR=1.01; 95% CI 0.71-1.45; P=0.949). Conclusions . BTXA improves muscle tone, physician global assessment, and disability assessment scale in upper limb spasticity and increases the Fugl-Meyer score in lower limb spasticity.